2004
DOI: 10.1023/b:toca.0000029756.50941.02
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene-Like Soot from EuroIV Diesel Engine: Consequences for Catalytic Automotive Pollution Control

Abstract: Soot particulates from an EuroIV diesel engine are sampled and investigated by high-resolution electron microscopy (HRTEM) and thermal gravimetry (TG). The experiments reveal a drastic reduction of primary particle size down to less than 20 nm, much smaller than that emitted by earlier diesel engines. HRTEM reveals primary particles with deformed fullerenoid structures. The defective fullerenoid soot is more prone to oxidation than the soot of a black smoking diesel engine. Our findings may initiate a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 4 publications
5
63
0
8
Order By: Relevance
“…The reactivity of diesel soot can vary widely with parameters such as the engine type [35], the fuel type [36,37], the engine load [38,39] and the presence of catalytically active ash species [40,41]. Numerous different types of soot are used in the oxidation studies in the literature, and the rate of catalytic soot oxidation scales with the inherent reactivity of the soot [23].…”
Section: Catalytic Soot Oxidationmentioning
confidence: 99%
“…The reactivity of diesel soot can vary widely with parameters such as the engine type [35], the fuel type [36,37], the engine load [38,39] and the presence of catalytically active ash species [40,41]. Numerous different types of soot are used in the oxidation studies in the literature, and the rate of catalytic soot oxidation scales with the inherent reactivity of the soot [23].…”
Section: Catalytic Soot Oxidationmentioning
confidence: 99%
“…It is reasonable to raise the question of whether the improved combustion conditions alter the microstructure of soot particulates and thus also change the reactivity towards oxidation, a question that is of importance both for combustion optimisation and for the after-treatment of soot. In a preliminary study we found that the microstructure of soot emitted from a low emission Euro IV HD diesel engine was different from that of a Euro III HD engine running in black smoke mode, and that consequently the oxidation behaviour of the soot was different [6]. In this paper we present the results of a comparative study on microstructure and oxidative behaviour of the Euro IV HD soot, spark-discharge soot (GFG), and hexabenzocoronene (HBC) stressing the significance of the microstructure-controlled oxidative property of Euro IV HD diesel soot and the possible consequence for air pollution controls.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low mass fraction of oxygen in soot carbon may be deceiving, since most of it is actually found on the surface in various functional groups, so that the soot particles do not behave as pure graphitic carbon in most atmospheric processes. The amount of oxygen at the surface of soot particles depends on combustion conditions, with more efficient combustion regimes resulting in higher abundance of oxygen and defective structures at the surface of the particles (Chughtai et al, 2002;Su et al, 2004). This in turn increases the chemical reactivity of the particles (including their thermochemical properties in soot analyzers) and their wettability in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The shapes and intensities of Raman transitions are functions of the graphite crystal size, morphology and sample composition (Sze et al, 2001;Sadezky et al, 2005). High resolution transmission electron microscopy (HRTEM) revealed that the internal structure of combustion soot spherules depends strongly on the chemical and thermal environment under which they are formed and on the time available for annealing (Buseck et al, 1987;Su et al, 2004). Very rapidly formed soot particles are nearly amorphous, with only some signatures of short-range order (Pósfai et al, 1999;Grieco et al, 2000;Ferry et al, 2002;Wentzel et al, 2003), with fullerenic structures developing at slightly longer residence times in the combustion region.…”
Section: Introductionmentioning
confidence: 99%